Strategy formulation and recommendation for “silverstone” synthetic leather apparel - Maharani, Tiara; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2018)
Abstract - Based on data from McKinsey Global Institute stated that consumer tendency in Indonesia in clothing shopping will tend to increase. Silverstone is one of the local brands engaged in the fashion industry of synthetic leather. Silverstone started his business since 2012. After struggling for 5 years finally Silverstone managed to expand its business. This is marked by an increase in sales figures. Since the beginning Naufal, the owner of Silverstone, runs this business alone. This is usually done in the early phase of business to minimize the cost to be incurred. As sales increase, Naufal needs a new strategy to enter the growth phase. The method used are observation and interview with the owner. In analyzing the internal factors researcher use Value Chain Analysis, Marketing Mix and assessment on existing Business Model Canvas. As for the external analysis researcher uses Porter's Five Forces and PESTEL. SWOT is a summary of internal and external company analysis (Silverstone). Company strategy is formulated by Quantitative Strategic Planning Matrix (QSPM) method based on IFAS AND EFAS matrix. The result of QSPM calculation, Silverstone suggested to use intensive strategy. This strategy aims to improve the company's competitive position with existing products. This strategy consists of market penetration, market development and product development. Silverstone also needs to establish an organizational structure to facilitate the strategy to be implemented. To grow into a big company, Silverstone have to implement its corporate strategy and functional strategy. Keywords : business strategy, clothing business, business model canvas